Internal flow and spray characteristics for elliptical orifice with large aspect ratio under typical diesel engine operation conditions. (15th September 2018) - Yu, Shenghao; Yin, Bifeng; Deng, Weixin; Jia, Hekun; Ye, Ze; Xu, Bin; Xu, Huaping
Highlights: Elliptical orifice had larger discharge coefficient as compared to circular orifice. The vorticity magnitude at the elliptical orifice exit was higher than circular one. Elliptical spray exhibited axis switching even at typical diesel engine conditions. The elliptical spray tip penetration was shorter than that of circular spray. The elliptical spray cone angle was larger than that of circular in all view planes. Abstract: The nozzle orifice geometry has great impact on the internal flow and spray characteristics, and thus affects the fuel-air mixture quality for diesel engines. This paper presents experimental and numerical research on the internal flow and spray behaviors with biodiesel for elliptical orifice with large aspect ratio and circular orifice of diesel nozzles, under high injection pressure and backpressure conditions. Large Eddy Simulation (LES) and Schnerr and Sauer cavitation model were adopted to study the internal flow, and the numerical models were validated firstly in terms of the mass flow rate, center line pressure and cavitation morphology. The elliptical spray images at the minor and major planes were acquired simultaneously with two CCD cameras through shadowgraph method. The results showed that the discharge coefficient of elliptical orifice was higher than that of circular orifice, which indicated that the elliptical orifice has better flow performance as compared to circular orifice. In addition, the vapor volume fraction at the circular orifice exit was larger than that of elliptical orifice, while the vorticity magnitudes were consistent lower than that of elliptical nozzle at the same injection pressure. And also, the elliptical orifice has more turbulence vortex structures near the nozzle exit than that of circular orifice, and the number of turbulence vortex structures increased as the injection pressure increases. Moreover, the cavitation distribution in the elliptical orifice in the direction of major axis shows longer length than that in the minor axis direction. The cavitation morphology at the elliptical orifice exit showed a unique horseshoe shape, while the cavitation morphology for circular orifice was still distributed symmetrically. Another important point is that the cavitation domain was similar with distribution of the turbulence vortex structures. Furthermore, the variation trend of elliptic spray cone angle proved that the elliptical spray underwent axis-switching even under high injection pressure and backpressure. Finally, the circular orifice spray held longer spray tip penetration in comparison to elliptical spray, while the elliptical exhibited much larger spray cone angle in all view planes. Because the elliptical spray underwent greater air dynamic drag induced by larger spray surface area. And the higher vorticity magnitude and more turbulence vortex structures at the elliptical orifice exit could also promote the initial spray breakup and thus inhibit the development of spray tip penetration. The axis-switching of elliptical spray can also increase the air entrainment ratio, which was conductive to increase the spray cone angle.